2016
DOI: 10.1159/000448134
|View full text |Cite
|
Sign up to set email alerts
|

Association between CT-Diagnosed Pneumonia and Endoscopic Submucosal Dissection of Gastric Neoplasms

Abstract: Background/Aims: This prospective cohort study aimed to elucidate the incidence and characteristics of pneumonia associated with endoscopic submucosal dissection (ESD) of gastric neoplasms using CT. Methods: We included consecutive 188 patients with gastric neoplasms treated with ESD. All patients underwent CT before ESD and the day after ESD. Pneumonia associated with ESD was defined as lung ground glass opacity or consolidation by CT the day after ESD. Results: In 188 patients, 28 patients had diabetes melli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 24 publications
2
21
2
Order By: Relevance
“…One study 16 identified male sex to be an independent risk factor for AP (2.835; 1.164–6.909), although the pooled estimates of five studies 11,12,16,19,31 revealed no significant association of sex with AP (1.22; 0.84–1.77; P = 0.30; I 2 = 32%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study 16 identified male sex to be an independent risk factor for AP (2.835; 1.164–6.909), although the pooled estimates of five studies 11,12,16,19,31 revealed no significant association of sex with AP (1.22; 0.84–1.77; P = 0.30; I 2 = 32%).…”
Section: Resultsmentioning
confidence: 99%
“…Of these records, 116 were excluded because of duplication, and 264 were excluded after screening for titles and abstracts. After the full‐text screening of the 114 records, 40 records 11–19,31–61 were finally considered eligible for inclusion in this systematic review. The details of the screening and exclusion processes are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopic submucosal dissection (ESD) emerged as an endoscopic treatment for gastrointestinal tumors in the 1990s and is now widely used as a beneficial curative therapy owing to its minimal invasiveness and good postoperative outcomes in activities of daily living. The use of ESD for superficial esophageal carcinoma is particularly advantageous in terms of postoperative activities of daily living compared with surgery [1][2][3]; however, a number of procedural accidents, including perforations, can occur during ESD [4][5][6]. The esophagus is anatomically characterized by the absence of a serosa, which means that mediastinal emphysema can occur with ESD, even without perforation [7,8].…”
Section: Introductionmentioning
confidence: 99%